Budgetprocessen i kommunal förvaltning : En fallstudie inom Luleå kommun - Sandgren Mella, Camilla (2011)
The budget process in the municipal organization is a complex institution in which administrations should follow the framework that the municipal council and city council has produced. Administrations then have the ability to internally distribute the framework how they want in their businesses and can determine their own internal budget process. If there are no clear rules on budget implementation process of the administration this could create differences between the administrations, since the decision makers internally in the administrations may have different views on the budget and budget process. Based on this reasoning, the research questions developed: how can the budget process in a municipality look like and what similarities and differences may exist between various levels of municipal administrations budget process in a local government. The purpose of this study was to identify how the budget process in a municipal administration might look like and also identify how the budget process in a municipality can look like. The purpose of this study also wanted to investigate whether there are any similarities and differences in process between different administrations. To get as good overall picture as possible of the administrations' budget process, this study focused on the financial responsibility of each administration. Interviews were conducted with each budget manager to identify similarities and differences between them. The results from this study are summarized; the first operation in the actual submission of the framework for administrations is the same between them. Differences can then occur in how the internal administrations decide to work out a plan, the setting and action plans within businesses. There have also been differences in both the monitoring and execution. Similarities between administrations have been traced to hierarchism-building activities, interim reports and accounting systems. Differences that emerged have been traced to various administrations of activity, size and ...